CULTURAL TOURISM - Dana POP (SEA: Practical Application of Science, 2016)

(untitled)
In this paper we will try to analyse the cultural tourism. We will start by referring to the complex concepts of tourism and culture and to the synergies existing between them. We will define cultural tourism and present its appearance and evolution as well as its importance as a modern form of tourism. We will present the various types of cultural tourism with their characteristics and the specific features of cultural tourists according to their interests. We will also mention that there are advantages and disadvantages for any kind of tourism depending on the position – local communities, companies or tourists. For the future we will refer to the new partnership between UNWTO and UNESCO.